Staff Use of Force in U.S. Confinement Settings: Lawful Control Tactics Versus Corporal Punishment - Martin, Steve J. (Social justice, 2006)
Part of a special issue on deaths in custody and detention. The writer discusses the pattern or practice of unlawful staff use of force in U.S, confinement settings that is cloaked with, or protected by, an air of legitimacy or facial validity. He asserts that it is not uncommon for ostensibly lawful applications of physical force to disguise the intentional infliction of punishment, retaliation, or reprisal on prisoners. He calls on courts to refuse to accept the logic that allows corrections professionals to modify the rule of law governing use of force in such a manner that it can be used to inflict corporal punishment on prisoners under the guise of an enforcement necessity to control them.